Usability Test Dengan Metode Eye Tracking Pada Website E- Learning Universitas Medan Area - Anangjasa, Trinaldo Sihotang; Sutrisno, Sutrisno; Silviana, Nukhe Andri (Mahesa Research Institute, 2024)
University of Medan Area (UMA) is one of the universities having an E-learning website for facilitating the teaching and learning process between students and lecturers that can be done remotely and connected via the internet. The features on the UMA E-Learning website are pretty complete, but still, the operation of some features is quite complicated and time-consuming, so some UMA students found it hard to use UMA E-Learning. The University of Medan Area E-Learning website needed to be tested for usability with Elements of Effectiveness and Efficiency. This study aimed to know the usability test results on the University of Medan Area E-Learning website and to know how the proposed improvements to the University of Medan Area E-Learning website. This research used the Eye Tracking method. Eye Tracking is a technique that allowed academics or researchers to analyze visual attention by detecting where users are looking, how long they are looking and the order in which they are looking. This test was carried out by giving several tasks to be done by the respondents, to find out the success and time of the respondents' work. The results in this study was based on the calculation of the effectiveness level in Task 1 obtained a percentage of 88.57%, Task 2 obtained 41.63%, and Task 3 obtained 48.57%. Based on the calculation of the efficiency level, it obtained TBE Task 1 = 0.038 goals/sec. TBE Task 2 = 0.024 goals/sec, TBE Task 3 = 0.031 goals/sec and obtained ORE Task 1 = 85.99%, ORE Task 2 = 29.83%, ORE Task 3 = 34.44%.